Assessment of Dietary and Lifestyle Responses After COVID-19 Vaccine Availability in Selected Arab Countries - Cheikh Ismail, Leila; Osaili, Tareq M.; Mohamad, Maysm N.; Al Marzouqi, Amina; Habib-Mourad, Carla; Abu Jamous, Dima O.; Ali, Habiba I.; Al Sabbah, Haleama; Hasan, Hayder; Hassan, Hussein; Stojanovska, Lily; Hashim, Mona; et al. (Frontiers in Nutrition, 2022)
Background: The COVID-19 pandemic has been consistently associated with unhealthy lifestyle behaviors and dietary practices. This study aimed to assess the dietary and lifestyle behaviors of adults after COVID-19 vaccine availability and their attitude towards the vaccine in selected Arab countries. Methods: A cross-sectional survey-based study was conducted between October 2021 and December 2021 using Google Forms (n = 2259). A multi-component questionnaire was used to collect socio-demographic characteristics, attitudes toward the COVID-19 vaccine, and behavioral, dietary, and lifestyle responses after easing the restriction. Participants were given a score based on the sum of positive dietary and lifestyle changes. The generalized linear models were used to identify the association between positive dietary and lifestyle changes score and sociodemographic characteristics. Results: Weight gain during the pandemic was reported by 39.5% of the participants, 36.1% reported ever getting infected with the COVID-19 virus, and 85% received at least one dose of the vaccine. The key adverse reactions of the COVID-19 vaccine were fatigue, headache, and joint pain, and the main reason for vaccination was protection against infection. Most participants were concerned about the vaccine side effects (45.8%) and inadequate testing (50.7%). After easing of restriction, 54.3% of the participants reduced the frequency of disinfecting objects, and 58.3% joined social events. Most dietary and lifestyle behaviors remained unchanged after vaccine availability but there was an increase in the time spent behind the screen for work (50.1%) and entertainment (42.9%). The results of the multivariate regression analyses revealed that older participants (p=0.001), those with higher education (p=0.010), and those working from home (p=0.040) were more likely to have higher positive dietary and lifestyle changes scores. Conclusions: Although most participants were concerned about vaccine safety, low vaccine hesitancy rates were observed among the study sample. The availability of the COVID-19 vaccines resulted in loosening some of the safety social measures among Arab adults but the negative impact of the pandemic on dietary and lifestyle behaviors remained unaltered.